The Effect of Festival Marketing on Consumer Perceptions at Shopee Double Days (Study on Wear Labels Consumer) - Martaputri, Fadhila Hana (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2023)
This research is intended to find out whether Festival Marketing affects Wear Labels Consumer Perception at Shopee Double Days. This research was conducted using a descriptive quantitative method, the population is Wear Label customers. Research data have been collected through questionnaires with a sample of 100 respondents using purposive sampling with female population characteristics aged 15-35 years. Data analysis was performed with a simple linear regression test using SPSS 25.0. This study resulted in the finding that Festival Marketing has a positive and significant effect on Wear Labels Consumer Perception at Shopee Double Days with an influence of 40.6%.